Milk production process, quality and technological properties of milk for the use of various types of milking machines - Lutsenko, Mariia; Halai, Oksana; Legkoduh, Victor; Lastovska, Iryna; Borshch, Oleksandr; Nadtochii, Valentyna (Acta Scientiarum. Animal Sciences, 2021)
Studies have been carried out to evaluate the efficiency of using easy-assembled cow houses in modern milk production technologies for the use of high-productive milking plants of the type ‘Parallel’ and ‘Carousel’ with 32 machines each. It has been established that new types of premises not only provide comfortable conditions for the maintenance of highly productive cows, but also reduce the labor costs for their maintenance and, most importantly, allow the use of modern high-productive milking installations of the type ‘Parallel’ and ‘Carousel’. It has been established that the technology of preparation of cows for milking and milking technology provides more complete display of the milk ejection reflex at the installation of the ‘Parallel’ type. The average intensity of cows’ milk flows at this plant is 30% higher compared to those of the installation of ‘Carousel’ type, which is confirmed by the intensity of milk flow production at the first minute of milking, which is at the level of 2.97 against 1.85 kg min.-1 per installation of ‘Carousel’ type. Milk obtained using a milking installation of the ‘Parallel’ type has higher values of the mass fraction of fat and protein that is associated with the genetic potential of animals. According to physical, chemical and technological properties, milk obtained from milking installations such as ‘Parallel’ and ‘Carousel’ is within the limits of the standards in force. Milk obtained from the use of milking equipment such as ‘Carousel’ has higher electrical conductivity at the level of 4.6 mS cm-3, which is confirmed by a higher level of mastitis disease of cows. Due to bacterial contamination, reductase test and milk clot characteristic, milk obtained using a milk installation of ‘Parallel’ type also has higher quality indicators than the installation of ‘Carousel’ type. But according to the complex of indicators, milk obtained from various technologies of milking refers to the desired cheese-making class.